Monte Carlo study on anomalous carrier diffusion in inhomogeneous semiconductors - Mori, N.; Hill, R.J.A.; Patanè, Amalia; Eaves, Laurence (IOP Publishing, 2015)
We perform ensemble Monte Carlo simulations of electron diffusion in high mobility inhomogeneous InAs layers. Electrons move ballistically for short times while moving diffusively for sufficiently long times. We find that electrons show anomalous diffusion in the intermediate time domain. Our study suggests that electrons in inhomogeneous InAs could be used to experimentally explore generalized random walk phenomena, which, some studies assert, also occur naturally in the motion of animal foraging paths.